Aberrant Hedgehog Signaling and Clinical Outcome in Osteosarcoma. (30th March 2014) - Lo, Winnie W.; Pinnaduwage, Dushanthi; Gokgoz, Nalan; Wunder, Jay S.; Andrulis, Irene L.
Abstract : Despite the importance of Hedgehog signaling in bone development, the relationship between Hedgehog pathway expression and osteosarcoma clinical characteristics and outcome has not been investigated. In this study of 43 high-grade human osteosarcoma samples, we detected high expression levels of the Hedgehog ligand gene, IHH, and target genes, PTCH1 and GLI1, in most samples. Further analysis in tumors of patients with localized disease at diagnosis identified coexpression of IHH and PTCH1 exclusively in large tumors. Higher levels of IHH were observed more frequently in males and patients with higher levels of GLI1 were more responsive to chemotherapy. Subgroup analysis by tumor size and IHH expression indicated that the well-known association between survival and tumor size was further refined when IHH levels were taken into consideration.